Effect of cultural practices on Alternaria blight in Brassica juncea and B.napus * - KUMAR, NEERAJ; KUMAR, ASHOK (The Indian Journal of Agricultural Sciences, 2011)
Studies were undertaken to investigate effect of date of sowing, fertilizer application, plant density and weed control on disease severity of Alternaria blight on Indian mustard [Brassica juncea (L.) Czem & Casson] and gobhi sarson (B.napus L.). Severity of altemaria blight on leaves and pods was significantly low in 1O ctober sown crop in comparison to later dates. Minimum disease severity of alternaria blight on leaves and pods was observed at 45 em row spacing, whereas disease severity was highest in broadcast method of sowing. Disease severity was significantly less in weeded treatments. The disease severity on leaves as well as on pods decreased, when K (40 kg/ha) was applied along with recommended dose ofN or S (40 kg/ha) was applied along with recommended NPK. 1 OOO-grain weight and yield was found to be highest when recommended NPK+S+FYM were applied.